2018
DOI: 10.14202/vetworld.2018.959-964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of cinnamon oil and sodium butyrate on carcass characteristics and meat quality of broiler chicken

Abstract: Aim:An in vivo experiment was conducted to investigate the effect of supplementation of cinnamon oil (CO) and sodium butyrate on carcass characteristics and meat quality of broiler chicken compared with the antibiotic supplementation.Materials and Methods:A biological experiment was carried out with 216-day-old Vencobb-400 broiler chicks randomly distributed to six experimental treatments with six replicates, each replicate containing six chicks with equal numbers of male and female chicks. The experimental di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
2
12
2
Order By: Relevance
“…Previous studies are also in favor of us, showing that essential oils and organic acids exert better overall carcass traits (Khattak et al, 2013;Peng et al, 2016;. While some researches are against our findings, no significant effect on carcass parameters was noticed (El-Shenway & Ali, 2016;Özsoy et al, 2017;Gomathi et al, 2018). This conflict of results may be due to variation in diet composition and breeds of broilers (Peng et al, 2016).…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies are also in favor of us, showing that essential oils and organic acids exert better overall carcass traits (Khattak et al, 2013;Peng et al, 2016;. While some researches are against our findings, no significant effect on carcass parameters was noticed (El-Shenway & Ali, 2016;Özsoy et al, 2017;Gomathi et al, 2018). This conflict of results may be due to variation in diet composition and breeds of broilers (Peng et al, 2016).…”
Section: Discussioncontrasting
confidence: 58%
“…As Devi et al [34] suggested, no significant differences in broiler carcass traits were recorded as affected by the addition of cinnamon and ajwain essential oils at levels of 3 and 4 g/kg of feed, respectively. In addition, Gomathi et al [51] reported that carcass characteristics such as ready-to-cook yield, abdominal fat, eviscerated, liver, gizzard, heart and giblet weights as a percentage of live body weight were not changed by the supplementation of cinnamon oil at levels of 250 or 500 mg/kg and coated sodium butyrate at 0.09% or 0.18% in broiler diets. In addition, the special aroma of cinnamon is desirable in poultry diets, and causes the elevation of the carcass content of unsaturated fatty acids and the alleviation of its content of SFA.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Abd El-Hack et al [ 2 ] believe that cinnamon can be used as a potential alternative to antibiotics in production conditions in the poultry industry. In addition, according to Gomathi et al [ 57 ], enrichment of the diet with cinnamon-based additives beneficially increases the amount of unsaturated fatty acids in the blood and muscle, thus reducing the pool of saturated acids. Lee et al [ 39 ], however, point out that diet supplementation with cinnamon aldehyde can reduce water intake by chickens, especially females, which can be dangerous in the case of laying hens.…”
Section: Discussionmentioning
confidence: 99%